The diapause program impacts renal excretion and molecular expression of aquaporins in the northern house mosquito, Culex pipiens. (April 2017) - Yang, Liu; Denlinger, David L.; Piermarini, Peter M.
Graphical abstract: Highlights: The diuretic capacity of diapausing Culex pipiens is significantly suppressed. Aquaporin mRNA levels in the renal excretory system are not reduced in diapause. Diapause impacts the aquaporin mRNA levels in non-excretory tissues. Abstract: Adult females of the mosquito Culex pipiens entering diapause increase sugar water ingestion and reduce evaporative water loss, but how these attributes of the diapause program impact activity of the renal excretory system remains unknown. Here we compared the renal excretory capacity of diapausing and non-diapausing females, as well as the molecular expression of aquaporin (AQP) genes that encode channels involved in transporting water and/or small metabolites. Baseline urine excretion rates in diapausing mosquitoes were higher than in those of their non-diapausing counterparts, possibly a consequence of the intense sugar feeding associated with diapause. But, diapausing mosquitoes exhibited a much lower capacity for diuresis than non-diapausing mosquitoes. The suppressed diuretic capacity likely reflects reduced investment in the energetically-expensive post-prandial diuresis, an event not observed in diapausing mosquitoes. The mRNA expression levels of two genes encoding AQPs, Eglp1 and Aqp12L, in diapausing mosquitoes were down-regulated (on day 14) and up-regulated (on both days 3 and 14), respectively, in whole body samples. These changes were not evident in the excretory system (i.e., Malpighian tubules and hindgut), which showed no differential expression of AQPs as a function of diapause. Several AQP mRNAs were, however, differentially expressed in the midgut, ovaries, and abdominal body wall of diapausing mosquitoes, suggesting that AQPs in these tissues may be playing important non-excretory roles that are unique to diapause physiology.